(untitled) (Circe de clásicos y modernos, 2018)
The De dogmatibus ecclesiasticis of Gennadius of Massilia is close to the tradition of symbols, easy to read doctrinal compilations, because of its structure and contents. The exam of Gennadius’ book contributes to define its composition context and its author’s dogmatic choices.